In Situ Spectroelectrochemical Investigation of Perovskite Quantum Dots for Tracking Their Transformation - Lee, ChaeHyun; Kim, Kyoungsoo; Shin, YeJi; Han, Donghoon; Yoon, Seog Joon (Frontiers in Energy Research, 2021)
All-inorganic lead-halide perovskite quantum dots (PQDs) (CsPbX3, where X is Cl, Br, or I) have been used successfully in optoelectronic applications, such as solar cells, light-emitting diodes, photocatalysts, and lasers. These PQDs work under electrochemical bias and/or illumination with charge separation/collection by interacting with the charge-transport medium. In this study, we discuss the spectroelectrochemical characteristics of PQDs to understand the oxidation and reduction processes that occur during photoinduced charge transport or charge injection under electrochemical conditions. We also found that the PQDs underwent irreversible transformation to the precursor state of plumbate complexes under electrochemical conditions. Furthermore, in-situ spectroelectrochemical analysis demonstrated that hole-mediated electrochemical oxidation of PQDs resulted in their irreversible transformation. Finally, the results presented herein contribute to our understanding of the charge-transfer-mediated process in PQDs and enhance their application potential in optoelectronic devices.